Enhancing playful interactions: eCoaching mothers of preschool children with disabilities - Amanda H. Passmore; Marie Tejero Hughes (Journal of Childhood, Education & Society)
Pretend play is crucial for developing communication and cognitive skills in preschool children. Targeted coaching during pretend play can effectively support family-centered practices and home-based assistance. This study employed a detailed collective case study to explore how eCoaching can aid family-centered practices during at-home pretend play for children with speech-language and developmental delays. Two mother-child pairs, each involving a preschool child with an Individual Education Plan (IEP), participated in at-home eCoaching sessions while engaging in pretend play. Implementing eCoaching helped mothers acquire play-based knowledge and better facilitate pretend play tailored to their child's developmental needs. Throughout the eCoaching process, improvements were noted in the children's quality of pretend play and language behaviors. After the eCoaching sessions concluded, both mothers and children experienced benefits from the process. The mothers had positive perceptions of their eCoaching sessions, found them easy to implement, and considered eCoaching beneficial for themselves and their children. This indicates that eCoaching is a socially valid family-centered practice. Future research should investigate how individual variables associated with the eCoaching influence child and family outcomes.